The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-33694/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UBA2 Activates Wnt/β-catenin Signaling Pathway during Protection of R28 Retinal Precursor Cells from Hypoxia by Extracellular Vesicles derived from Placental Mesenchymal Stem Cells

Abstract: Abstract Background: Stem cell transplantation has been proposed as an alternative treatment for intractable optic nerve disorders characterized by irrecoverable loss of cells. Mesenchymal stem cells, with varying tissue regeneration and recovery capabilities, are being considered for potential cell therapies. To overcome the limitations of cell therapy, we isolated exosomes from human placenta–derived mesenchymal stem cells (hPMSCs), and investig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… Aires et al (2020) reported that exosomes produced by retinal microglia under high intraocular pressure can propagate the inflammatory signals and promote retinal degeneration. Another two groups found that exosome derived from human placental MSCs and human 293T cells which express brain-derived neurotrophic factor (BDNF) can protect R28 cells (retinal precursor cells that represent RGCs) from hypoxia injury ( Koh et al, 2020 ; Yan et al, 2020 ).…”
Section: Exosomes In Retinal Diseasementioning
confidence: 99%
“… Aires et al (2020) reported that exosomes produced by retinal microglia under high intraocular pressure can propagate the inflammatory signals and promote retinal degeneration. Another two groups found that exosome derived from human placental MSCs and human 293T cells which express brain-derived neurotrophic factor (BDNF) can protect R28 cells (retinal precursor cells that represent RGCs) from hypoxia injury ( Koh et al, 2020 ; Yan et al, 2020 ).…”
Section: Exosomes In Retinal Diseasementioning
confidence: 99%